Rancang Bangun Sistem Informasi Helpdesk dan Ticketing Internal IT Berbasis Web pada PT Solusi Teknologi Unggul - Mohamad Taufik Wibowo; Farizi Ilham; Fabian Jason Song; M. Dwi Reza Maulana (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2026)
PT Solusi Teknologi Unggul requires a structured internal information technology service management process, particularly for reporting and resolving hardware, software, and network issues. The previous process was still conducted manually through WhatsApp or direct communication, which caused poor documentation, difficulty in tracking ticket status, unstructured technician assignment, and limited performance evaluation. This study aims to design and develop a web-based Internal IT Helpdesk and Ticketing Information System using the Waterfall method. The system is developed using PHP, MySQL, Apache, and XAMPP, and provides ticket management, status tracking, priority and Service Level Agreement (SLA), technician assignment, knowledge base, email notification, and analytical dashboard modules. The design results indicate that the system can centralize issue reporting, document resolution history, improve ticket-status transparency, and support management in monitoring IT service performance more effectively.